Hydrocarbon‐Soluble Piperazine‐Containing Dilithium Anionic Initiator for High Cis‐1, 4 Isoprene Polymerization. Issue 1 (29th August 2017) - Schultz, Alison R.; Bobade, Sachin; Scott, Philip J.; Long, Timothy E.
Abstract: The synthesis of 1, 4‐bis[4‐(1‐phenylethenyl)benzyl] piperazine and subsequent reaction with sec ‐butyllithium enables a novel piperazine‐containing difunctional organolithium initiator for the living anionic polymerization of isoprene. Piperazine provides a polar unit within the difunctional initiator, promoting ion dissociation and miscibility with hydrocarbon solvents, and enabling the formation of well‐defined polyisoprene homopolymers with predictable molecular weights and controlled microstructure. In situ Fourier transform infrared spectroscopy monitors the dilithium initiator formation and the anionic polymerization of isoprene, revealing kinetic insight into this synthetic method. Furthermore, sequential monomer addition with styrene affords poly(styrene‐ block ‐isoprene‐ block ‐styrene) triblock copolymers with controlled molecular weights and narrow polydispersities. This novel initiator facilitates the synthesis of thermoplastic elastomers with desired cis ‐1, 4 microstructure in polydienes. Abstract : The synthesis of 1, 4‐bis[4‐(1‐phenylethenyl)benzyl] piperazine and subsequent reaction with sec ‐butyllithium produces a novel, hydrocarbon‐soluble dilithium initiator. This enables facile synthesis of well‐defined isoprene‐containing block copolymers with high cis‐ 1, 4 microstructure and low polydispersity.